Using critical discourse analysis to explore an authentic teaching material: A focus on language and power - Sukma Septian Nasution; Nur Najibah Sukmawati; Azhar Aziz Lubis; Tommy Hastomo; Lodya Sesriyani (Universitas Syiah Kuala, 2020)
Many EFL students show anxiety when speaking English in Indonesia. Therefore, when it comes to pedagogical context, critical discourse analysis (CDA) has a significant role to explore linguistics unit, socio-cultural context, and ideology of the text learners need to understand. This study aims at analysing the relation of language and power behind a text entitled ‘Driving Age, Increasing’ and making use of it to pedagogical context. The chosen text is an authentic material adopted from ‘Debatabase’, a book on building argumentative skills. By using Fairclough’s model (1989), the text was examined through three steps of Critical Discourse Analysis (CDA), namely description, interpretation, and explanation. Then, the analysis is interrelated with the nature of discussion text taught to the learners. The result of the analysis shows that the text is dominated by material, verbal, and relational processes, formal, complex, repetitive, evidence-based, multi-perspective, and over-wording dictions underpinned in an institutionalized social activity and unspecialized semantic domain. Further, the relationship between the author and the readers indicates there is equality in power shown by the provided equal analytical perspectives and evidence-based arguments to both conflicting parties toward the issue. As it fits the nature of discussion text, the paper ends with recommendations for EFL teachers to make use of CDA in raising learners’ language awareness.